Zinc Adsorption Kinetics Using Pseudomonas as Biomass - Hidayat, Hidayati; Suyono, Yoyon (Biopropal Industri, 2014)
Zinc adsorption kinetics using Pseudomonas aeruginosa and Pseudomonas sp. was conducted to determine the ability of biomass to adsorb Zinc, and also to get the biosorption equilibrium and kinetics. Adsorption process conducted in this study was using batch method with variables on the amount of biomass (0.01 g, 0.02 g, 0.03 g, 0.04 g and 0.05 g), adsorption time (30, 60 and 120 min) and pH (4 and 6). Zinc metal biosorption kinetics following the pseudo-second-order equation. The highest correlation coefficient obtained on the condition of 0.04 g biomass for both pH 4 and pH 6 was 0.999. The best Zinc metal adsorption equilibrium models obtained at pH 4 with contact time at 60 minutes. This heavy metal adsorption equilibrium models comply the Freundlich isothermal with a correlation coefficient (R2) of 0.973.